2011
DOI: 10.1007/s12011-011-9079-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Sb(V) in a Human Macrophage Cell Line Measured by HPLC-ICP-MS

Abstract: Drugs based on pentavalent antimony are first-line treatment of the parasite disease leishmaniasis. It is generally believed that Sb(V) acts as a prodrug, which is activated by reduction to Sb(III); however, the site of reduction is not known. It has been hypothesised that the reduction takes place in the parasites' host cells, the macrophages. In this study, the human macrophage cell line Mono Mac 6 was exposed to Sb(V) in form of the drug sodium stibogluconate (Pentostam™). Cell extracts were analysed for Sb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Reduction of the pro-drug Sb V to the bioactive Sb III has been shown to occur both in Leishmania amastigotes and host cells, but not promastigotes [10, 39, 40]. Thus, alterations in host cell drug uptake and metabolism could directly impact exposure of the intracellular parasite to the drug, parasite survival and the efficacy of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the pro-drug Sb V to the bioactive Sb III has been shown to occur both in Leishmania amastigotes and host cells, but not promastigotes [10, 39, 40]. Thus, alterations in host cell drug uptake and metabolism could directly impact exposure of the intracellular parasite to the drug, parasite survival and the efficacy of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A marine macroalga, Sargassum sp., was the first reported organism able to reduce Sb(V) in seawater (59). In the treatment of leishmaniasis, several studies suggested that Sb(V), when used as a prodrug medicine, might be reduced in both the vertebrate host and the parasites (60)(61)(62)(63). However, the knowledge of bacterial Sb(V) reduction is limited.…”
Section: Microbial Antimony Cyclementioning
confidence: 99%
“…It also increases ROS production in a human macrophage cell line (Hansen et al, 2011), causing parasite death. In the case of inorganic species of Sb, the toxicity mechanisms have not been studied in depth, and all mechanisms that have been raised are due to phys-icochemical similarities with As (De Boeck et al, 2003), suggesting that Sb can generate the aggregation of proteins and DNA damage, similar to As (Beyersmann and Hartwig, 2008;Tamás et al, 2014).…”
Section: Introductionmentioning
confidence: 99%